2017
DOI: 10.1002/asia.201701287
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)‐Catalyzed Directed C−H Amidation of N‐Nitrosoanilines and Subsequent Formation of 1,2‐Disubstituted Benzimidazoles

Abstract: An efficient rhodium-catalyzed direct C-H amidation of N-nitrosoanilines with 1,4,2-dioxazol-5-ones as amidating agents has been developed. This method featured mild reaction conditions, a wide substrate scope and satisfactory yields. Besides, the amidated products could be readily converted to pharmaceutically valuable 1,2-disubstituted benzimidazoles via an HCl-mediated deprotection/cyclization process in one pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…The optimized reaction conditions employing 3 mol% Rh(III), 12 mol% AgSbF 6 , and 15 mol% NaOAc in n ‐heptane gave a variety of ortho ‐amidated nitrosoanilines (Scheme 19). [24] This study demonstrated that N ‐nitrosoanilines bearing EDGs and EWGs smoothly and gratifyingly promoted the reaction in the presence of aryl‐ or alkyl‐ substituted dioxazolones, regardless of their electronic properties, to give the target product in excellent yield. Later, Chen and co‐workers developed the C−H amidation of N ‐nitrosoanilines using 1,4,2‐dioxazol‐5‐ones under ball‐milling conditions.…”
Section: Rhodium‐catalyzed C−h Functionalizationmentioning
confidence: 76%
“…The optimized reaction conditions employing 3 mol% Rh(III), 12 mol% AgSbF 6 , and 15 mol% NaOAc in n ‐heptane gave a variety of ortho ‐amidated nitrosoanilines (Scheme 19). [24] This study demonstrated that N ‐nitrosoanilines bearing EDGs and EWGs smoothly and gratifyingly promoted the reaction in the presence of aryl‐ or alkyl‐ substituted dioxazolones, regardless of their electronic properties, to give the target product in excellent yield. Later, Chen and co‐workers developed the C−H amidation of N ‐nitrosoanilines using 1,4,2‐dioxazol‐5‐ones under ball‐milling conditions.…”
Section: Rhodium‐catalyzed C−h Functionalizationmentioning
confidence: 76%
“…Rh(III)-Catalyzed ortho-amidation of Nnitrosoaniline was performed using 1,4,2-dioxazol-5-ones as an amidating agent in presence of AgSbF 6 (12 mol%) and NaOAc (15 mol%) in n-heptane (Scheme 16, Condition A). [45] This protocol facilitated the synthesis of a series of benzamides with both electron-donating and -withdrawing substituents in moderate to good yields. The reaction is irreversible as no deuterium incorporated product was isolated from the control experiment using CD 3 OD under standard condition.…”
Section: Carbonà Nitrogen Bond Formationmentioning
confidence: 99%
“…An efficient ortho ‐amidation of N ‐nitrosoanilines was developed by Pan group in 2017. Rh(III)‐Catalyzed ortho ‐amidation of N ‐nitrosoaniline was performed using 1,4,2‐dioxazol‐5‐ones as an amidating agent in presence of AgSbF 6 (12 mol%) and NaOAc (15 mol%) in n ‐heptane (Scheme 16, Condition A) [45] . This protocol facilitated the synthesis of a series of benzamides with both electron‐donating and ‐withdrawing substituents in moderate to good yields.…”
Section: Carbon−nitrogen Bond Formationmentioning
confidence: 99%
“…For the activation of aniline derivatives a nitroso 74 or a pyrimidyl group 77 can be used as a DG. Pan et al [31a] . used nitroso as a DG for N ‐alkyl anilines to get amidation products 75 with dioxazolones 7 (Scheme 26a).…”
Section: Cp*rh(iii)‐catalyzed Directed Ortho Sp2(c)−h Amidation or Ammentioning
confidence: 99%